The impact of training and development on employees performance of Davao sugar central company INC. in Guihing, Hagonoy, Davao del sur - Degamo, Almavilla D.; Gumboc, Sarah Faye L.; Sumacle, Charelie (--Digos City: UM Digos College, 2016)
This study focuses on the impact of training and development. Training and development is a critical process, which seeks to improve the performance of workers in the organization. In order to form competent committees, employee's relevant expertise and intellectual capacity needs to be improved. Moreover the ineffectiveness of training and development of employee in the organization reduce the organization productivity as organization depend on having people with right skills, attitudes and capabilities in order to teach goals effectively. The finding of the study reveals that: there is a significant relationship of the level of training and development and the level of employees in Davao sugar central company incorporated. The researchers conclude that a good training and development programs help to keep the right people and grow profit. As the battle for top talent becomes more competitive, employee training and development programs are more important than ever and hiring top talents takes time and money.